Frequency-hopped multiple-access communications with noncoherent M-ary OFDM-ASK. - Al-Dweik, A. (IEEE Transactions on communications)
A noncoherent, bandwidth-efficient modulation scheme is proposed for frequency-hopping multiple-access (FH-MA) networks. The proposed scheme is a combination of noncoherent M-ary amplitude-shift keying (NMASK) and orthogonal frequency-division multiplexing (OFDM). Using this scheme minimizes the required data bandwidth. The number of frequency slots available to the users increases significantly for a fixed spread-spectrum bandwidth (BWSS). The effect of the multiple-access interference is reduced. Simple and accurate bit error rate expressions have been derived for FH-OFDM-MASK in additive white Gaussian noise channels and for FH-OFDM-ASK in Rayleigh fading channels.